Using codes based on weighted multiplication without division for correction of the trough-bys "packet" errors in wireless channels - Марковский, А. П.; Клименко, И. А.; Саидреза, Мехмали (Problems of Informatization and Control, 2011)
We propose a method for quick-fix "stack" errors in the wireless data transmission channels. The method is based on a weighted control codes, calculated using the mathematical operation of multiplication by a binary job evaluation without hyphenation. The proposed method allows to accelerate and reduce the computational complexity of the correction procedure, as compared to the Reed-Solomon codes, and compared to known codes based on the weighted checksums. A mathematical justification of the proposed method, described correction procedure error bursts is given a numerical example. The method focuses on the use of modem communication systems real-time data